Effects of Physical–Skilful Exercises on Improving Muscular Strength of the Arms and Shoulder and the Skilful Performance of the MOY upon Parallel Device - Ghazi, Hydar; Tariq, Zyiad (Journal of Physical Education, 2015)
This study aims at being acquainted with the following: the effects of physical–skilful exercises on improving muscular strength of the arms and shoulder at the post test of the experimental group; the Skilful Performance of the MOY upon Parallel Device at the post test of the experimental group and the significant differences between physical–skilful exercises and the skilful performance between the experimental groups at post tests. Methods and procedures: the sample included 12 gymnasts with ages of 11-13 year representing the youth team Ninaveh state. The sample was divided by lot into two groups with 6 subjects each. The procedures were completely applied including tests and assessing the skilful performance pre and post the suggested exercise programs and under the same situations. The experimental method was used since it convenient to the nature of the study. The procedure included also a questionnaire offered to experts to determine certain physical and skilful exercises and the proper test for them. The equality and homogeneity of were achieved between two groups in variables of age, high, weight, physical, skilful and performance pre tests. In addition, some pilot studies were applied to avoid problems and difficulties at the exercises. After that, the pre and post test of the physical and skillful exercises of the performance were applied. Then, the two groups experienced the suggested programs built for them which they lasted 8 weeks with three sessions a week. The post tests were applied with same procedures. Conclusions: this study concluded that the Physical –Skilful Exercises have positive effects upon improving muscular strength of the arms and shoulders and the skillful performance. Recommendation: it is necessary to use the physical –skilful exercises on improving muscular strength of the arms and shoulder upon parallel device